Pneumatic Retinopexy for Early Rhegmatogenous Retinal Detachment - Tehseen Mehmood Mahju, Irfan Qayyum Malik, Ch. Javed Iqbal, Yasir Afzal, Nasir Ch. (Pakistan Journal of Ophthalmology, 2015)
Purpose: The purpose of this study was to evaluate the success rate of pneumatic retinopexy in the patients of early rhegmatogenous retinal detachment. Material & Methods: The study was performed at Ophthalmology Department of Gujranwala Medical College/ Teaching Hospital. All the Patients were admitted from outpatient department. Retinal examination with confirmation of all retinal pathology was done by using indirect Ophthalmoscope and three mirror indirect lens. Topical anesthesia or a retrobulbar block was used for patient comfort. Laser photocoagulation was applied in attached areas of retina. Intraocular gas was injected. SF6 was drawn into tuberculin syringe to provide tamponade to the detached retina. Intraocular pressure was assessed by checking the pulsations at optic disc and by checking the light perception. Antibiotic steroid ointment was applied and eye was patched. Postoperatively Argon laser was reinforced close to the break in all the cases to seal the break. Patients were followed up for six months. Anatomical reattachment of the retina was our primary outcome. Results: 15 patients of early rhegmatogenous detachment were included in this study, 9 were male and 6 were females. All the patients had single retinal break at superior quadrant. After pneumatic retinopexy 10 patients had attached retina till their last follow up of six months. The success rate of pneumatic retinopexy was 66%. Rest of the five patient required further surgery. Conclusion: In selected cases of early rhegmatogenous retinal detachment pneumatic retinopexy is an effective and less expensive procedure that avoids most of the complications that usually occur with other retinal reattachment procedures. Key Words: Pancreatic Retinopathy, Retinal Detachment, Intraocular Gas.